The Pyrus sinkiangensis Yu PsLEA4 Gene Enhances the Cold Resistance of Solanum lycopersicum - Xueying Yang; Wenjuan Zhao; Hui Li; Zhenxia Zhao; Jianbo Zhu; Jin Li (Plants)
Plants have large amounts of the late embryogenesis abundant protein (LEA) family of proteins, which is involved in osmotic regulation. The Korla Pear (Pyrus sinkiangensis Yu) is an uncommon pear species that thrives in Xinjiang and can survive below-freezing conditions. We found that the PsLEA4 gene was more expressed after cold treatment by looking at the transcriptome data of the Korla Pear. In order to evaluate the biological function of the PsLEA4 protein under low-temperature stress and its potential for use in agricultural breeding, we cloned the PsLEA4 gene from the Korla Pear, made a plant overexpression vector, and transformed it into a tomato via Agrobacterium transformation. When exposed to low temperatures, we found that PsLEA4 overexpression can regulate proline metabolism and antioxidant enzyme activity in tomatoes compared to wild tomatoes. Because of this, transgenic tomatoes are more resilient to cold temperatures and produce more than their wild counterparts. Thus, expressing PsLEA4 has multiple advantages: (1) Improving frost resistance and reducing plant damage. (2) Increasing crop yield. Therefore, this study provides a theoretical basis for the role of the PsLEA4 protein in plants’ resilience to low temperatures, as well as for its potential application in crop breeding.